The effect of problem-based learning on students’ critical thinking and speaking competence - Utama, I Made Permadi; Imansyah, Imansyah (Universitas Sarjanawiyata Tamansiswa, 2022)
This study is generally attempted to find the effect of Problem-Based Learning towards students’ critical thinking and speaking competence at SMA Muhammadiyah Mataram. This research applied experimental research using MANOVA. The population of this research was the students of SMA Muhammadiyah Mataram. The sample of the study was 29 students consisting of two classes. The results of the study show that there is a significant effect of Problem-Based Learning towards students‟ critical thinking and speaking. Research data found that the mean score of critical thinking was 74,50 and class control was 54,00; 0,05. While the mean for the speaking of the experimental class was 75.83 and control class was 60,45; 0,05. It can be concluded that the use of Problem Based Learning has a positive effect on students‟ critical thinking and speaking competence and has correlation both of them at the SMA Muhammadiyah Mataram.